Analisis Kebutuhan Sumur Resapan Sebagai Upaya Konservasi Air Tanah Pada Perumnas Nendagung Kota Pagar Alam - Barrorotul Azizah (JURNAL ILMIAH BERING'S, 2017)
Water that is universal or comprehensive from every aspect of life becomes more valuable both in terms of quantity and quality. However, land use change due to indirect housing development can damage water catchment. One way to maintain water quantity is to apply absorption wells. The presence of absorption wells will have an impact on reduced surface runoff. The rainwater that originally fell onto the surface of the tile does not flow directly to the elegance or the home page but is flowed through the zinc and continues to be accommodated into the absorption well. The effect that can be felt is that rainwater does not spread to the yard or the elegance so as to reduce the occurrence of surface runoff.